The psychophysics of learning : implications for learning systems design and configuration - Moye, John N. (Emerald Publishing Limited, 2021)
The Psychophysics of Learning presents a learning system design approach that is formulated by the strategies and techniques the brain uses to process external information and make sense of that information to the learning ecology of all learners. The psychophysics of sensation, perception, and cognition provide the research information, which is used to formulate the learning system framework. These processes are inherent to all individuals and result in a model that promotes access, learning, and academic success for all learners. This information is applied to the design of the learning engagement, learning experience, and learning environment dimensions of a learning system. The psychophysics of sensation are applied to the design of the learning engagement strategies to ensure that all learners can intellectually access and comprehend the information presented as inputs to the learning system. The psychophysics of cognition are applied to the development of learning environments that integrate and internalize the external learning into the unique cognition of each learner. The resulting system creates a learning system design that is aligned with the natural learning processes of the brain.